2014
DOI: 10.3382/ps.2014-03881
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of embryos to cyclically cold incubation temperatures durably affects energy metabolism and antioxidant pathways in broiler chickens

Abstract: Cyclically cold incubation temperatures have been suggested as a means to improve resistance of broiler chickens to ascites; however, the underlying mechanisms are not known. Nine hundred eggs obtained from 48 wk Ross broiler breeders were randomly assigned to 2 incubation treatments: control I eggs were incubated at 37.6°C throughout, whereas for cold I eggs the incubation temperature was reduced by 1°C for 6 h daily from 10 to 18 d of incubation. Thereafter, chickens were reared at standard temperatures or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The increased SOD activity with LOW-Inc indicated the ability to scavenge free radicals and inhibit the oxygen free radical production which may be a part of epigenetic adaptation mechanism. These results were consistent with previous results obtained in broiler chicks (Loyau et al, 2014).…”
Section: Thyroid Functions and Antioxidant Enzyme Activities Of Chicksupporting
confidence: 94%
“…The increased SOD activity with LOW-Inc indicated the ability to scavenge free radicals and inhibit the oxygen free radical production which may be a part of epigenetic adaptation mechanism. These results were consistent with previous results obtained in broiler chicks (Loyau et al, 2014).…”
Section: Thyroid Functions and Antioxidant Enzyme Activities Of Chicksupporting
confidence: 94%
“…Broilers are sensitive to temperature variations and their metabolic rate will rise to adapt to colder conditions [18], and thereby leading to the growth inhibition and even death [3]. Low ambient temperature is reported to induce hypoxia and ascites in broilers due to the increase of oxygen demands for both fast growth and heat production [3].…”
Section: Discussionmentioning
confidence: 99%
“…Incubation parameters such as temperature [2], light [3] or noise [4] are known to impact development and behavior. In a context of climate change, with an increase of global average temperature and the occurrence of extreme heatwaves [5], numerous studies have reported the utilization of the thermal-manipulation (TM) of eggs during the incubation period to improve the later-life heat tolerance of chickens [2,[6][7][8][9][10][11][12][13][14][15][16] and turkeys [17,18] or to modify muscle development in ducks [19][20][21]. The TM consists in a modification of the incubation temperature of avian eggs during embryogenesis, which is often cyclic and applied during defined periods of the embryonic development.…”
Section: Introductionmentioning
confidence: 99%